The Effects of Natural Antioxidant Extracts Supplementation on Performance and Meat Quality of Broiler Chickens - Ishola, Hakeem; Jiya, Elisha Zhiri; Adama, J.Y; Alabi, Olushola John (Journal of Agricultural Sciences (Belgrade), 2020)
The study examined the effect of dietary antioxidant supplementation on performance and meat quality of broiler chickens. 300 day old Abhor acre broiler chicks were fed starter diet from 1-4 weeks and finisher diet for the last 4weeks. Birds were randomly assigned to treatments based on antioxidants supplementation in drinking water at 0.02% butylated hydroxyanisole (BHA), ordinary water (OW), 0.02% sweet orange peel extracts (SOPE), 0.02% shaddock peel extracts (SHPE) and 0.02% lemon peel extracts (LMPE) per litre of water in a completely randomized design experiment. Feed intake and body weight gain were recorded on weekly basis. 3 birds were selected in each treatment and slaughtered for meat quality determination. Despite treatment (OW) having the best feed intake, which was significantly different (P
Keywords: Synthetic Antioxidant, Natural Antioxidants, Feed Intake, Weight Gain, Sensory Parameters